Psychoanalysis of the Characters in ScHneider’s The Beginning of Everything - Agung Diah Sri Utami, I Gusti Ayu (Humanis; Vol 22 No 4 (2018), 2018)
The title of this study is Psychoanalysis of the Characters in Schneider’s The Beginning of Everything where its aim was to find out the characterization of the characters, as well as the three major personalities concerning the Id, Ego, and Superego of the characters that are presented in the novel. The data in this study were taken from a novel entitled The Beginning of Everything written by Robyn ScHneider in 2013. The data were collected by using the documentation method supported by the note taking technique. In analyzing the data, the study applied the qualitative method and supported by the narrative descriptive technique.The theories used were two different kinds, the first one is from How to Analyze Fiction proposed by Kenney (1966), the second one is Theory of Psychoanalysis proposed by Freud (1896). The result of the study shows that the characterization of the characters could change according to the situations they are facing. The relationship between the Id, Ego, and Superego that was mentioned by Freud are applied in the novel where it has influenced every decision taken by the characters.